Peningkatan Kematangan Proses TI: Penilaian, Rekomendasi dan Validasi (Studi Kasus Sistem Informasi IPOS) - Setiyowati Setiyowati; Sri Siswanti; Andriani Kusumaningrum; Kumaratih Sandradewi (STMIK Sinar Nusantara, 2019)
IPOS information system is a service delivery system (package) and letter (mail) PT Pos Indonesia. The application of the IPOS information system still found problems, the problem of human resources, bar codes that were not in accordance with the delivery receipt. So it is necessary to do an assessment of the IPOS information system, the purpose of this study is to determine the level of maturity of the system information, formulate recommendations for improvements if needed and validation recommendations. The framework used assessment is COBIT 4.1 framework, focus DS10 process (Managing Problems) and DS11 (Managing Data). The results of the assessment will be obtained maturity level, then the formulation of recommendations for increasing maturity is carried out, then validation of the recommendations proposed. Data collection techniques with observation, interviews, study of business documents, literature studies, and questionnaires. Data is processed based on COBIT framework rules 4.1. The results of the DS10 and DS11 process assessments are at Level 3 (Defined), management has been managed well but its implementation is still not maximal. Recommended improvements to DS10 and DS11 as 3 recomendation. The results of the recommendation validation are in the score 4 to 6, is capable with great effort